Inner views of grief the stories of five bereaved young people - Johnson, Juanita Swan; Good Mourning (Firm) (Boston, MA : Fanlight Productions, 1995)
When young people experience the death of a loved one, the adults in their lives sometimes fail to understand what an overwhelming experience this can be. In this compelling new video, documenting a panel discussion with Juanita Johnson, five young adults from ages 14 to 26 discuss their reactions to the sudden, sometimes violent death of a parent, sibling, or friend
Title from title screen
This discussion was presented as part of a two day conference,'When crisis strikes the school community,' sponsored by Good Mourning Center for Life transition and loss in November, 1994, Binghamton, New York
Panel discussion leader: Juanita Johnson
DVD format
Keywords: Grief -- Psychological aspects; Bereavement -- Psychological aspects